Postpartum Depression: Molecular Insights and AI-Augmented Screening Techniques for Early Intervention - Mahesh Recharla; Karthik Chava; Chaitran Chakilam; Sambasiva Rao Suura (International Journal of Medical Toxicology and Legal Medicine, 2024)
Postpartum depression (PPD) constitutes a complex and multifaceted mental health condition affecting a significant proportion of women following childbirth, with profound implications for maternal well-being, infant development, and familial dynamics. This work delves into the molecular underpinnings of PPD, exploring the intricate interplay of hormonal fluctuations, immune system dysregulation, and genetic susceptibilities in precipitating the disorder. Advances in neurobiological research have illuminated the roles of serotonin signaling, hypothalamic-pituitary-adrenal axis alterations, and inflammatory cytokines in shaping the pathology of PPD, offering potential biomarkers for identification and intervention. Despite these advances, traditional methods of screening and diagnosis often fall short, hampered by subjective assessments, underreporting, and limited accessibility, thereby underscoring the urgent need for innovative approaches. In response to these challenges, this discussion introduces the integration of artificial intelligence into PPD screening and intervention frameworks, presenting a paradigm shift toward precision mental healthcare. Leveraging machine learning algorithms and natural language processing models, AI-driven systems have demonstrated remarkable potential in identifying subtle linguistic, behavioral, and physiological patterns indicative of postpartum depression. These technologies transcend the limitations of purely clinical judgment, enabling scalable, non-invasive, and adaptive tools that enhance early detection and personalized care. By synthesizing molecular insights with AI-guided methodologies, this review seeks to foreground the critical intersections of biology and technology in addressing postpartum depression, offering a pathway to mitigate its impact through targeted, proactive strategies. In doing so, it advocates for a multidisciplinary approach that bridges neuroscience, data science, and public health to revolutionize mental health outcomes for postpartum women globally.